PRINCIPLES OF ENGINEERING DYNAMICS: CONCISE THEORY AND APPLICATIONS - Waluyo Adi Siswanto (Penerbit UTHM, 2008)
This book cover the kinematics and kinetics of particles followed by the kinematics and kinetics of rigid bodies In the theory parts, only concise explanations with pictures are given in this book and avoid complicated mathematical explanations for new readers. Selected problems related to the topics are then presented in complete solutions to improve and to comprehend some basic theories related to the real applications. This pedagogical approach may improve a better understanding when students refer to books suggested in the references. The presentation of the example problem is explained in two approaches; a plain explanation and the corresponding symbolic programming codes. In every example problem, the solution strategy is discussed and followed by the detail calculation and results. The solution is accompanied by Mathcad solution codes written in a two-column style. The left column explains the solution approach, relevant equations, calculation procedures and the results, whereas Mathcad solution codes are written in the right column.